2019
DOI: 10.1002/anie.201910277
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Enhancement of Upconversion by Negative Lattice Expansion in Orthorhombic Yb2W3O12

Abstract: Thermal quenching of photoluminescence represents a significant obstacle to practical applications such as lighting, display, and photovoltaics. Herein, a novel strategy is established to enhance upconversion luminescence at elevated temperatures based on the use of negative thermal expansion host materials. Lanthanide‐doped orthorhombic Yb2W3O12 crystals are synthesized and characterized by in situ X‐ray diffraction and photoluminescence spectroscopy. The thermally induced contraction and distortion of the ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
66
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 195 publications
(66 citation statements)
references
References 48 publications
0
66
0
Order By: Relevance
“…[9][10][11][12][13][14][15] Especially, it is highly pivotal for multifunctional sensing to achieve multistimuli responsive luminescence such as humanmachine interfaces, multiple strains, and magnetic fields sensing. [16][17][18][19][20] Due to the convenience of molecular design, organic fluorescent dyes have many advantages in realizing multiresponsive emissions. By integrating different functional units or using molecule interactions, organic dyes have been confirmed to possess multiple luminescence forms including ML, persistent luminescence, PL.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15] Especially, it is highly pivotal for multifunctional sensing to achieve multistimuli responsive luminescence such as humanmachine interfaces, multiple strains, and magnetic fields sensing. [16][17][18][19][20] Due to the convenience of molecular design, organic fluorescent dyes have many advantages in realizing multiresponsive emissions. By integrating different functional units or using molecule interactions, organic dyes have been confirmed to possess multiple luminescence forms including ML, persistent luminescence, PL.…”
Section: Introductionmentioning
confidence: 99%
“…These methods, however, require multiple excitation sources and stringent control over crystalline phase, chemical composition, and surface ligands. Variations in the thermal field also allow reversible luminescence modulation of UCNPs, though these are impractical for device configuration 20 , 21 . External stimulus-responsive hosts, such as liquid crystal polymer networks, ferroelectric or optomagnetic materials, have been studied to manipulate emission dynamically under external electrical or magnetic stimulation 22 25 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Zou et al reported a strategy for enhancing photon upconversion at high temperatures by taking advantage of negative thermal expansion host materials. They reported a 29-fold enhancement of green upconversion luminescence in the Er 3+ -doped orthorhombic Yb 2 W 3 O 12 crystals when temperature is increased from 303 to 573 K. 4 Also, authors have focused on uncommon thermal quenching effects in thermochromic materials and Covalent Organic Frameworks (COF). Mazza et al have shown that the spontaneous opening and closing of oxazine heterocycles might become a viable mechanism to design uorescence sensors capable of responding ratiometrically to temperature.…”
Section: Introductionmentioning
confidence: 99%